Cutaneous Perforators and Their Clinical Implications on Intrinsic Hand Flaps: A Systematic Review - Theddeus Octavianus Hari Prasetyono, MD, PhD; Clara Menna, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
Background:. Most hand flaps are local intrinsic flaps because hand perforators are small and fragile. The purpose of this review was to gather anatomical data on cutaneous perforators of the hand and their implications on intrinsic hand flaps. Methods:. An electronic search was performed through PubMed, Scopus, ScienceDirect, ProQuest, and CINAHL in April 2021. The search terms included “hand,” “palm,” “manus,” “cutaneous artery,” “angiosome,” and “perforasome.” Studies were filtered according to the PRISMA flow chart, and critically appraised using the Quality Appraisal for Cadaveric Studies (QUAC) and Appraisal Tool for Cross-sectional Studies (AXIS). Results:. A total of 33 studies were included, of which 20 were pure anatomical studies, 10 combined anatomical and clinical studies, and three imaging-based clinical studies. A total of 643 hands and 406 fingers were included. The dorsal aspect of the hand, the dorsal digits, hypothenar, midpalm, thenar, and dorsal wrist consistently have adequate, closely distributed perforators of small diameters and short pedicle lengths. A series of clinical studies proved the success of elevating local perforator flaps on each of these areas. Conclusions:. The hand contained densely interlinked cutaneous perforators of varying sizes and pedicle lengths. Although some areas of the hand are still unexplored, knowledge on cutaneous perforators of the hand allows the creation of a variety of possibilities for intrinsic hand flap designs.